2018
DOI: 10.1016/j.ijrmms.2017.11.016
|View full text |Cite
|
Sign up to set email alerts
|

Blast wave induced spatial variation of ground vibration considering field geological conditions

Abstract: This work is licensed under a Creative Commons Attribution-NonCommercial-NoDerivatives 4.0 International licence Newcastle University ePrints -eprint.ncl.ac.uk Gui YL, Zhao ZY, Jayasinghe LB, Zhou HY, Goh ATC, Tao M. Blast wave induced spatial variation of ground vibration considering field geological conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(12 citation statements)
references
References 42 publications
(51 reference statements)
0
11
0
1
Order By: Relevance
“…For example, R. Nategh [10] studied the attenuation of PPVs on the surface for different types of explosives, detonators, and rocks. Y. L. Gui et al [11] researched the propagation of blasting vibrations in rock stratum and rock-soil strata through field tests and finite element simulations. U. Ozer [12] fitted the PPVs and the distance from the explosion source under different rocks.…”
Section: Introductionmentioning
confidence: 99%
“…For example, R. Nategh [10] studied the attenuation of PPVs on the surface for different types of explosives, detonators, and rocks. Y. L. Gui et al [11] researched the propagation of blasting vibrations in rock stratum and rock-soil strata through field tests and finite element simulations. U. Ozer [12] fitted the PPVs and the distance from the explosion source under different rocks.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of blasting energy is used on the movement of rock fragments, heat, noise, and seismic vibrations. Concerning the stability and integrity of the rock mass and adjacent structures, the blasting-induced ground vibration has the most critical effect (Liu et al, 2017;Hu et al, 2018;Gui et al, 2018;Xu et al, 2019;Gou et al, 2020;Zorzal et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…In the few decades, amounts of researches have been carried out to study the response of structure to the blasting activities in tunnel constructions, such as the field tests, indoor experiments, numerical simulation, artificial intelligence [9][10][11][12][13][14][15][16][17]. Hong [18] studied the dynamic impact of cross section blasting excavation at intersections on the lining of existing tunnels, and the results showed that the maximum vibration velocity and the maximum tensile stress of each section of the lining were greatly reduced out of the range of ±8 m at the cross section, and the lining structure was more sensitive to blasting within the range of ±8 m around the blasting source.…”
Section: Introductionmentioning
confidence: 99%